BIOFILM: FORMATION AND NATURAL PRODUCTS’ APPROACH TO CONTROL – A REVIEW. - OSUNGUNNA, Michael Oluwole (African Journal of Infectious Diseases (AJID), 2022)
Biofilm formation, especially on indwelling medical devices such as catheters, can result in infections and substantially affect patients’ quality of life. Biofilm-associated infections have led to increased morbidity and mortality, increased cost of treatment, and length of hospital stay. However, all of the identified consequences of the biofilm-associated infections had been attributed to the reduced susceptibility of biofilm to conventional antimicrobial agents which has necessitated the development of a new strategy for biofilm infections control, thereby making a search for more effective antimicrobial agents from plant source inevitable. So far, some antimicrobial agents (crude or isolated compounds) from plant sources affect a specific stage of biofilm development while a few of them have been developed into a suitable dosage form for biofilm control. In this review, an attempt is made to look into some definitions of biofilm by "biofilmologists", stages in biofilm formation, mechanisms of resistance in biofilm, biofilm control strategies, the use of some natural products in biofilm control and concepts of probiotics as agents of biofilm control.